Modeling of Gas-to-Particle Mass Transfer in Turbulent Flows - Garrick, Sean C. (SpringerBriefs in Thermal Engineering and Applied Science,, 2018)
This Brief focuses on the dispersion of high-porosity particles, their entrainment into the vapor-laden stream, and the condensation of vapor onto the particles. The authors begin with a simple/static problem, focusing on transport within the particle. They go on to consider the high-resolution simulation of particles in a turbulent flow and the time-dependent evolution of the fluid-particle fields. Finally, they examine the more computationally-affordable large-eddy simulation of gas-to-particle mass-transfer. The book ends with a summary and challenges as well as directions for the area.